(untitled) (Marketing Journal, 2026)
This article examines ethical standards for the collection and processing of consumer data in international marketing research in the context of digital transformation. The study is theoretical and analytical in nature and is based on a comparative assessm ent of international professional standards (ICC/ESOMAR, GDPR, ISO 20252) and the personal data protection legislation of the Republic of Uzbekistan. The research applies comparative and GAP analyses, as well as risk -based and contextual approaches, to ide ntify factors affecting the practical implementation of ethical requirements. The findings demonstrate that existing regulatory gaps and ethical risks are systemic and are intensified by digitalization and cross -border data flows. The study substantiates t he need for an integrated and context -adaptive approach to managing ethics in marketing research.